Influence of Microgap Location and Configuration on Peri-implant Bone Morphology in Nonsubmerged Implants: An Experimental Study in Dogs - Weng, Dietmar; Nagata, Maria José Hitomi [UNESP]; Bell, Matthias; Nascimento de Melo, Luiz Gustavo; Bosco, Álvaro Francisco [UNESP] (Quintessence Publishing Co Inc, 2010)
Purpose: It is unknown whether different micro gap configurations can cause different pen-implant bone reactions. Therefore, this study sought to compare the peri-implant bone morphologies of two implant systems with different implant-abutment connections. Materials and Methods: Three months after mandibular tooth extractions in six mongrel dogs, two oxidized screw implants with an external-hex connection were inserted (hexed group) on one side, whereas on the contralateral side two grit-blasted screw implants with an internal Morse-taper connection (Morse group) were placed. on each side, one implant was inserted level with the bone (equicrestal) and the second implant was inserted 1.5 mm below the bony crest (subcrestal). Healing abutments were inserted immediately after implant placement. Three months later, the peri-implant bone levels, the first bone-to-implant contact points, and the width and steepness of the peri-implant bone defects were evaluated histometrically. Results: All 24 implants osseointegrated clinically and histologically. No statistically significant differences between the hexed group and Morse group were detected for either the vertical position for peri-implant bone levels (Morse equicrestal -0.16 mm, hexed equicrestal -0.22 mm, Morse subcrestal 1.50 mm, hexed subcrestal 0.94 mm) or for the first bone-to-implant contact points (Morse equicrestal -2.08 mm, hexed equicrestal -0.98 mm, Morse subcrestal -1.26 mm, hexed subcrestal -0.76 mm). For the parameters width (Morse equicrestal -0.15 mm, hexed equicrestal -0.59 mm, Morse subcrestal 0.28 mm, hexed subcrestal -0.70 mm) and steepness (Morse equicrestal 25.27 degree, hexed equicrestal 57.21 degree, Morse subcrestal 15.35 degree, hexed subcrestal 37.97 degree) of the pen-implant defect, highly significant differences were noted between the Morse group and the hexed group. Conclusion: Within the limits of this experiment, it can be concluded that different microgap configurations influence the size and shape of the peri-implant bone defect in nonsubmerged implants placed both at the crest and subcrestally. INT J ORAL MAXILLOFAC IMPLANTS 2010;25:540-547
Keywords: bone morphology; equicrestal placement; histometric study; microgap; subcrestal placement